Geology, geochemistry, geochronology and petrogenesis of the Archean TTG and leucogranite suítes from Rio Maria domain, southeast of Amazonian Craton - Almeida, José de Arimatéia Costa de (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2013)
Teses